2016
DOI: 10.1098/rsob.160038
|View full text |Cite
|
Sign up to set email alerts
|

Systematic tracking of altered haematopoiesis during sporozoite-mediated malaria development reveals multiple response points

Abstract: Haematopoiesis is the complex developmental process that maintains the turnover of all blood cell lineages. It critically depends on the correct functioning of rare, quiescent haematopoietic stem cells (HSCs) and more numerous, HSC-derived, highly proliferative and differentiating haematopoietic progenitor cells (HPCs). Infection is known to affect HSCs, with severe and chronic inflammatory stimuli leading to stem cell pool depletion, while acute, non-lethal infections exert transient and even potentiating eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 49 publications
8
29
0
Order By: Relevance
“…In contrast, the proliferation rates of both MPPs and HSCs were only statistically consistent with controls until day 3, before dramatically increasing by day 5 ( Figure 1D). As we previously reported (Vainieri et al, 2016), LK cell numbers were significantly reduced by day 7, while MPP numbers were substantially increased, and the number of HSCs remained essentially unchanged throughout the course of infection ( Figure 1E). The observation that the HSC compartment does not grow in size during infection, even though the proportion of HSCs entering S-phase does, suggests that HSCs produce an increased number of differentiated progeny.…”
Section: P Berghei Infection Affects the Dynamics Of The Entire Hsc supporting
confidence: 84%
See 2 more Smart Citations
“…In contrast, the proliferation rates of both MPPs and HSCs were only statistically consistent with controls until day 3, before dramatically increasing by day 5 ( Figure 1D). As we previously reported (Vainieri et al, 2016), LK cell numbers were significantly reduced by day 7, while MPP numbers were substantially increased, and the number of HSCs remained essentially unchanged throughout the course of infection ( Figure 1E). The observation that the HSC compartment does not grow in size during infection, even though the proportion of HSCs entering S-phase does, suggests that HSCs produce an increased number of differentiated progeny.…”
Section: P Berghei Infection Affects the Dynamics Of The Entire Hsc supporting
confidence: 84%
“…In parallel with the development of innate and adaptive immune responses, infections and inflammatory cytokines stimulate haematopoietic stem and progenitor cells (HSPCs) to modify the composition of their progeny to cope promptly with the increased demand for mature cells (Essers et al, 2009;Esplin et al, 2011;MacNamara et al, 2011). A range of dramatic HSPC responses have been noted as a result of these insults, including an expansion of the early progenitor compartment (identified as Lineagec-Kit + Sca-1 +, or LKS), and alterations in cycling properties, long-term function and migration patterns of HSCs (Baldridge et al, 2010;Rashidi et al, 2014;Matatall et al, 2016;Vainieri et al, 2016). These phenomena all take place within the bone marrow (BM) microenvironment, yet very little is currently known about the response of HSC niche cells to infection and inflammation, and what their role may be in regulating the observed changes in haematopoietic dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By integrating intravital microscopy, computational analysis of images, flow cytometry and mathematical modelling, Cristina Lo Celso (Imperial College London, UK) addressed how stresses such as infection or leukemia influence normal blood cell generation in situ. Cristina showed that during infection, HSCs become either motile (although not mobilized) or very still, and that the flux through HSC and progenitor (HSPC) populations is likely to be dramatically altered (Vainieri et al, 2016). Furthermore, results presented by Delfim Duarte from her laboratory highlighted the increasing migratory behavior of leukemia cells from early bone marrow infiltration to overt chemoresistance and their relationship with bone marrow niches known to maintain HSCs (Hawkins et al, 2016).…”
Section: Hematopoietic Stem Cells In the Adultmentioning
confidence: 94%
“…These parasites continue to shed soluble antigens, hemoglobin metabolites and derivatives that drive various syndromes of malaria like SMA. This may explain the continued decline in hematologic indices despite the evidently low parasitemia and the malarial anemia pathogenesis, which implicates bone marrow dysfunction as displayed by low reticulocytosis [16,17]. When Hb decreases, the normal body physiology upregulates the bone marrow erythroid progenitors and reticulocytes are increased as an indicator of this process.…”
Section: Definitions Of Severe Malarial Anemiamentioning
confidence: 99%